"Subestimamos las habilidades de los estudiantes:" Bilingual teacher candidates building on multilingual assets. Issue 1 (2nd January 2022) - Briceño, Allison; Zoeller, Emily
ABSTRACT: Teaching for equity with bilingual learners means building on students' linguistic strengths. This critical qualitative self-study explored how pre-service bilingual teachers developed ideology and pedagogy through a structured, holistic approach to writing instruction. Seven bilingual teacher candidates implemented a strategic Transliteracy approach to writing instruction, observing student assets and teaching cross-linguistically. Data includes semi-structured interviews and coursework. Findings showed teachers' ideological and pedagogical clarity co-developed as they implemented a holistic biliteracy practice. Implications for bilingual teacher education include (1) providing opportunities for teacher candidates to practice assets-based formative assessment and instruction; (2) employing a holistic biliteracy orientation; and (3) creating spaces to develop ideology and pedagogy that dismantles harmful monolingual paradigms, practices, and norms.